2020
DOI: 10.1155/2020/4610128
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Oblique Lumbar Interbody Fusion with Lateral Screw Fixation and Transforaminal Full-Endoscopic Lumbar Discectomy (OLIF-TELD) and Posterior Lumbar Interbody Fusion (PLIF) for the Treatment of Adjacent Segment Disease

Abstract: Background. A potential long-term complication of lumbar fusion is the development of adjacent segment disease (ASD), which may require surgical intervention and adversely affect outcomes. A high incidence of recurrent ASD was reported in patients who underwent the second (repeat) PLIF for symptomatic ASD. Herein, a feasible method, oblique lumbar interbody fusion combined with transforaminal endoscopic lumbar discectomy (OLIF-TELD) for dealing with adjacent lumbar disc herniation with upward or downward migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Various techniques for interbody fusion, including TLIF and OLIF, have been developed [ 2 , 4 , 12 , 13 , 14 , 29 ]. Several clinical studies and a few meta-analyses have compared postoperative outcomes and complications between the two techniques, TLIF and OLIF [ 3 , 5 , 6 , 7 , 8 , 14 , 26 , 30 , 31 , 40 , 41 , 42 , 43 , 44 ]. However, previous studies did not control for the preoperative conditions requiring lumbar fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various techniques for interbody fusion, including TLIF and OLIF, have been developed [ 2 , 4 , 12 , 13 , 14 , 29 ]. Several clinical studies and a few meta-analyses have compared postoperative outcomes and complications between the two techniques, TLIF and OLIF [ 3 , 5 , 6 , 7 , 8 , 14 , 26 , 30 , 31 , 40 , 41 , 42 , 43 , 44 ]. However, previous studies did not control for the preoperative conditions requiring lumbar fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral-access cage insertion techniques via the retroperitoneal space have been invented to reduce the problems related to TLIF procedures, including lateral lumbar interbody fusion (LLIF) or oblique lateral interbody fusion (OLIF) [ 2 , 4 , 7 , 11 , 12 , 13 , 14 , 15 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. LLIF is conducted via the intermuscular approach dissecting the psoas muscle; thus, it can cause psoas muscle-related complications, including anterior thigh pain, leg weakness, nerve root injury, and others [ 2 , 4 , 11 , 13 , 14 , 25 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…OLIF is characterized by minimally invasive, high fusion rate, and low complications ( 28 , 29 ). It has been widely used in spinal degenerative scoliosis ( 30 , 31 ), spondylolisthesis ( 18 ), spinal stenosis ( 32 ), ASD ( 33 , 34 ), and DBP ( 14 ), and has achieved good clinical effects. This study further confirmed the well early and mid-term effects of OLIF in the treatment of DBP.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior internal fixation with pedicle screws is thought to have an excellent capacity to stabilize the fused segment due to the high stiffness of the structure and thus has been widely used in the field of spinal surgery. Compared to the posterior approach, in situ screw fixation through the LLIF incision can avoid changes in the patient's position during the operation, the need for a second incision, and injury to the spinal cord and nerve by the pedicle screws 30 . Furthermore, previous biomechanical studies have demonstrated that lateral instrumentation has a good ability to enhance the overall stability and has reasonable biomechanical protection, similar to pedicle screws 8 .…”
Section: Discussionmentioning
confidence: 99%